2020
DOI: 10.1371/journal.pone.0243531
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics in Mexico: A diagnostic from the academic perspective and recommendations for a public policy

Abstract: In this work, we present a diagnostic analysis of strengths, weaknesses, opportunities and threats (SWOT) of the current state of Bioinformatics in Mexico. We conducted semi-structured interviews among researchers and academics with key expertise in this field, identified by bibliometric analyses and qualitative sampling techniques. Additionally, an online survey was conducted reaching a higher number of respondents. Among the relevant findings of our study, the lack of specialized human resources and technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Although research output in genomics and bioinformatics has significantly increased in the last decade in Latin America, impact and quality is still a matter of concern. A comparative analysis of the data presented here with similar initiatives in other Latin American countries (Blas et al, 2011;Bicudo, 2016;De Las Rivas et al, 2019;Zambrano-Mila et al, 2019;Armenta-Medina et al, 2020) has revealed some interesting patterns. One of them is the recognition for a better characterization of the genetic structure of the region's population, a theme that can be deeply explored by genomics and bioinformatics.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although research output in genomics and bioinformatics has significantly increased in the last decade in Latin America, impact and quality is still a matter of concern. A comparative analysis of the data presented here with similar initiatives in other Latin American countries (Blas et al, 2011;Bicudo, 2016;De Las Rivas et al, 2019;Zambrano-Mila et al, 2019;Armenta-Medina et al, 2020) has revealed some interesting patterns. One of them is the recognition for a better characterization of the genetic structure of the region's population, a theme that can be deeply explored by genomics and bioinformatics.…”
Section: Discussionmentioning
confidence: 62%
“…Recent studies suggest the challenges have not changed. For example, recent research conducted in Mexico revealed that experts in Bioinformatics believe the lack of technological infrastructure and human resources are deficiencies in the research area (Armenta-Medina et al, 2020). Another study carried out by consulting experts in the field revealed that researchers from different regions of Brazil deal with unequal access to sequencing platforms, especially for the country's northern area (Bicudo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, a depth study of bioinformatics development is necessary per country. Previous work explored the scientific productivity and situational diagnosis from the academic perspective in Mexico [ 13 ], but did not perform an integral analysis including productivity, conceptual structure, and thematic evolution of the research in the field. Understanding the conceptual structure of the area as well as its thematic evolution will help to reveal the dominant, transversal and emerging themes of national bioinformatics, generating a map on which strategies can be developed to exploit the most relevant themes, strengthen emerging ones and promote those relatively new concerning the international context.…”
Section: Introductionmentioning
confidence: 99%